Instrument-Based Estimation of Full Treatment Effects with Partial Compliers - Nibbering, Didier; Oosterveen, Matthijs (The Review of Economics and Statistics, 2024)
Abstract The effect of the full treatment is a primary parameter of interest in policy evaluation, while often the effect of a subset of treatment is estimated. We partially identify the local average treatment effect of receiving full treatment (LAFTE) using an instrumental variable that may induce individuals into subsets of treatment (partial compliers). We show that partial compliers violate the standard exclusion restriction, necessary conditions on the absence of partial compliers are testable, and partial identification holds under a double exclusion restriction. We identify partial compliers in four applications and estimate informative bounds on the LAFTE in three of them.